The Stem Cell Club: a model for unrelated stem cell donor recruitment. Issue 12 (24th September 2017) - Fingrut, Warren; Parmar, Simran; Cuperfain, Ari; Rikhraj, Kiran; Charman, Erin; Ptak, Emilie; Kahlon, Manjot; Graham, Alice; Luong, Susan; Wang, Yongjun (George); Yu, Janice; Arora, Neha; et al.
Abstract : BACKGROUND: Patients with blood, immune, or metabolic diseases may require a stem cell transplant as part of their treatment. However, 70% of patients do not have a suitable human leukocyte antigen match in their family, and need an unrelated donor. Individuals can register as potential donors at stem cell drives, where they provide consent and a tissue sample for human leukocyte antigen typing. The ideal donors are young, male, and from a diversity of ethnic backgrounds. However, in Canada, non‐Caucasian males ages 17 to 35 years represent only 8.8% of listed donors. STUDY DESIGN AND METHODS: The Stem Cell Club is a non‐profit organization founded in 2011 in Canada that aims to augment recruitment of the most needed donors. The initiative published a recruitment toolkit online (www.stemcellclub.ca ). Currently, there are 12 chapters at universities across Canada. RESULTS: To date, the Stem Cell Club has recruited 6585 potential registrants, representing 1.63% of donors on Canada's donor‐database. Of the recruited registrants, 58.3% were male; 60.3% of males self‐reported as non‐Caucasian, and 78.5% were ages 17 to 25 years. From 2015 to 2016, the initiative recruited 13.7% of all ethnically diverse males ages 17 to 35 years listed in Canada's donor database. Data from this initiative demonstrate sustainability and performance on key indicators of stem cell drive quality. CONCLUSION: The Stem Cell Club has developed a capacity to recruit 2600 donors annually, with the majority being males with a high degree of ethnic diversity. The initiative enhances the quality of Canada's unrelated donor‐database, improving the chances that patients in need of an unrelated donor will find a match for transplant. The Stem Cell Club is a model relevant to recruitment organizations around the world.